Convergence analysis of an inertial algorithm for generalized mixed equilibrium problems and Bregman quasi asymptotically nonexpansive mappings - Umar, L.; Haruna, L.Y.; Tafida, M.K. (International Journal of Mathematical Analysis and Modelling, 2023)
The aim of this article is to introduce an inertial algorithm for approximating solution of a system of generalized mixed equilibrium problem and common fixed point of countable families of Bregman quasi asymptotically nonexpansive mappings. The strong convergence theorem has been establish in reflexive Banach spaces. Our results are significant improvement of some recent results announced in the literature.